Production of reduced calorie structured lipid by acidolysis of tripalmitin with capric acid: optimisation by response surface methodology - Bektas, Inan; Yucel, Sevil; Ustun, Guldem; Aksoy, H. Ayse (WILEY, 2008)
BACKGROUND: Structured lipids (SLs) containing medium-chain fatty acids (C8:0-C12:0) in the 1- and 3-positions and long-chain fatty acids in the 2-position of triacylglycerols have interesting applications as reduced calorie fats. The aim of this study was to produce an SL by inserting capric acid (CA, C8:0) into tripalmitin (TP) and to optimise the reaction conditions by response surface methodology (RSM) with a three-level, three-factor face-centred cubic design. RESULTS: Lipozyme TL IM from Thermomyces lanuginosa was used for the acidolysis of TP with CA in n-hexane. The effects of three independent parameters, namely substrate molar ratio, enzyme amount and reaction time, on CA incorporation into TP were optimised. The range of each parameter was selected as follows: substrate molar ratio (CA/TP), 4-8; enzyme amount, 9-15 wt% of total substrate; reaction time, 6-10 h. Optimal conditions were determined to be a CA/TP molar ratio of 6.5, an enzyme amount of 11.6 wt% and a reaction time of 8.9h. Experiments conducted under these optimised conditions yielded an SL containing 35.7 wt% (44.9 mol%) CA. A second-order polynomial model was obtained for CA incorporation. CONCLUSION: The possibility of enriching CA in TP by enzymatic acidolysis has been established. The SL containing 44.9 mol% CA produced under optimal conditions may be considered a reduced calorie fat. (C) 2008 Society of Chemical Industry.
Keywords: acidolysis; capric acid; lipozyme TL IM; reduced calorie structured lipid; response surface methodology; tripalmitin; LIPASE-CATALYZED ACIDOLYSIS; DOCOSAHEXAENOIC ACID; OIL; TRIACYLGLYCEROLS; LARD; RICH; DHA; Agriculture; Chemistry; Food Science & Technology